Nástroje pro přechod na oběhové hospodářství Informační, motivační a dobrovolné nástroje pro obce a občany - Tóthová, Dominika (Masaryk University Press, 2020)
Title in English: Instruments for the transition to a circular economy: Information, motivational and voluntary instruments for municipalities and citizens. The publication deals with instruments that can be used to transition municipalities to a circular economy. It identifies possible information, motivation and voluntary instruments, which can be used particularly by representatives of municipalities to support citizens to environmentally friendly behavior, waste prevention and use of other available means of circular economy.